Queens of Langkasuka - Nimibutr, Nonzee; Sahamongkol Film International ([Thailand] : Sahamongkol Film International, 2008)
Faced with the potential invasion their kingdom, the Queen and her two sister princesses of Langkasuka must band together to protect their realm. Princes of neighboring dynasties have formed a coalition with rebel pirates, plotting to seize the powerful cannon. The mass destruction juggernaut is much coveted by any party seeking to tip the balance of power to their advantage. Artillery is deployed, the infantry is mobilized and the Doo Lam force is unleashed. Determined to defend their people and their land, the sisters are even willing to put their lives on the line
Cast: Sorapong Chatree, Ananda Everingham, Winai Kraibutr, Jakrit Panichpatikam, Jesdaporn Pholdee, Attaporn Teemakorn
VCD format
Malay subtitle
Keywords: Historical films; Fantasy films